Urinary tract infection and hyperbilirubinemia - Bilgen, Hülya; Ozek, Eren; Unver, Tamer; Biyikli, Neşe; Alpay, Harika; Cebeci, Dilşat (The Turkish Journal of Pediatrics, 2006)
The aim of this study was to evaluate the incidence of urinary tract infection (UTI) in newborns with asymptomatic, unexplained indirect hyperbilirubinemia in the first two weeks of life. Jaundiced infants, otherwise clinically well, less than two weeks of ages, with a total bilirubin level above 15 mg/dl were eligible for the study. A bilirubin work-up including glucose-6-phosphate dehydrogenase (G-6 PD) level, as well as urinalysis and a urine culture were performed in all patients. Patients with UTI, defined as more than 10,000 colony-forming units per milliliter of a single pathogen obtained by bladder catheterization, were evaluated for sepsis. Renal function tests and renal ultrasound were performed in cases with UTI. During follow-up, voiding cystourethrogram (VCUG) and dimercaptosuccinic acid scintigraphy (DMSA) were performed as well. A total of 102 patients were enrolled. The bilirubin work-up of patients did not demonstrate any significant underlying disorder. None of the infants had a high direct bilirubin level. UTI was diagnosed in eight (8%) cases [Enterobacter aerogenes (3/8:38%), Enterococcus faecalis (2/8:25%), Klebsiella pneumoniae (2/8:25%) and Escherichia coli (1/8:12%)]. Of those eight patients, only four (50%) had pyuria. Bacteriuria was present in seven (88%) patients. The sepsis screen was negative in all but one case with a high C-reactive protein (CRP) level. None of the patients had a positive blood culture. Renal function tests were within normal levels in all patients. Renal ultrasound showed urinary tract abnormalities in three (38%) patients (hydronephrosis, n=1 and pelviectasis, n=2). VCUG was performed in all patients during the study period and one had unilateral grade 3-4 reflux, while only one patient had a diverticulum of the bladder. DMSA was performed in seven patients and none had renal scars. It is of importance that UTI can occur in asymptomatic, jaundiced infants even in the first week of life. Although it is well known that UTI is a common cause of prolonged jaundice, urine culture should be considered in the bilirubin work-up of infants older than three days of age with an unknown etiology.